Zr < 4 + >-doped aY2O3-bYCr0. 5Mn0. 5O3 thermal sensitive ceramic material and preparation method thereof
By doping Zr4+ in Y2O3-YCr0.5Mn0.5O3 thermosensitive ceramics, a solid solution is formed, which solves the problem of high porosity during sintering, and achieves the high density and electrical stability of the ceramics.
Patent Information
- Application Number
- CN202411702228.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing negative temperature coefficient thermosensitive ceramics have a high porosity problem during the sintering process, which affects the consistency and electrical properties of the ceramics.
By doping Zr4+ to Y2O3-YCr0.5Mn0.5O3 thermosensitive ceramics, a (Y1-xZrx)2O3 solid solution is formed, reducing the melting point and sintering temperature, reducing the formation of pores, and dry-cool isostatic molding and high-temperature sintering process are used to form a solid solution of (Y1-xZrx)2O3, reducing the melting point and sintering temperature, reducing the formation of pores, and the dry-cool isostatic molding and high-temperature sintering process , improve the density of ceramics.
It significantly reduces the porosity of thermistor ceramics, improves its density and electrical properties stability, and enhances the consistency of the ceramics.
Smart Images

Figure CN119462150A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic material preparation, and particularly relates to a Zr 4+ Doped Y2O3-YCr 0.5 Mn 0.5 O3 thermistor ceramic material and preparation method thereof. Background Art
[0002] Negative Temperature Coefficient Thermosensitive Ceramics (NTC) is a semiconductor material with a negative temperature coefficient, whose resistance value decreases as the temperature increases. Negative temperature coefficient thermistors are widely used in the automotive, aviation, and navigation fields due to their high sensitivity, high stability, and low cost. The working principle of NTC thermistors is based on the temperature characteristics of semiconductor materials. At room temperature, the resistance of NTC materials is relatively high. As the temperature increases, the concentration of carriers (electrons or holes) in the material increases, resulting in a decrease in resistance. NTC materials are usually made of metal oxides (such as manganese oxide, nickel oxide, etc.), and their resistance characteristics are adjusted through appropriate doping and sintering processes.
[0003] In the existing market, most of the negative temperature coefficient thermistors are spinel structures, and the operating temperature range is from room temperature to 350°C. However, thermistors with perovskite structures can be used at operating temperatures above 350°C, even up to 1000 degrees, and can be better used in high-temperature environments such as the metallurgical industry and automobile exhaust emissions. The perovskite NTC ceramics of the Y-Cr-Mn-O system are used in exhaust gas detection systems in high-temperature environments due to their high accuracy, high heat resistance, and wide detection range. The materials of the Y-Cr-Mn-O system are composed of high-resistance phase Y2O3 and semiconductor phase YCr 1-x Mn x O3 composition. YCr 1-x Mn x O3 is a perovskite structure, which is doped with Mn on the basis of YCrO3 perovskite structure. 3+ After formation, through Mn 3+ The amount of Y2O3 can regulate its resistivity and thermal constant. At the same time, Y2O3 is a rare earth oxide with high resistance, high thermal stability and stable chemical properties. 1-x Mn x O3 compound can improve the stability of thermal sensitive devices at high temperatures.
[0004] NTC components are small in size and volume. In actual production, ceramic blanks with larger volumes are usually prepared and then cut and thinned to obtain chips with a thickness of several hundred micrometers. This requires that each small chip obtained has a uniform composition distribution and fewer pores, so that the resistance of each chip is not much different (this is also called the consistency of NTC thermistors), thus meeting the requirements of mass production. The presence of pores will directly affect the change of resistance and lead to non-uniform resistance values.
[0005] Patent CN115849898A discloses a thermosensitive ceramic material, its preparation method, and a thermistor. The invention provides a body-centered cubic perovskite-like structure CaCu3Ti doped with metal M 12 , with the molecular formula CaCu3Ti 4-x M x O 12 , where M is selected from at least one of Y, Al, Zr, and Mn, and 0 < x ≤ 0.6. By preparing an aqueous solution containing Ca 2+ , Cu 2+ , and the doped ion M, the doped ion M is selected from at least one of Y 3+ , Al 3+ , Zr 4 +, and Mn 2+ , and preparing a solution containing a Ti 4+ ion complex; mixing and stirring the aqueous solution and the solution containing the Ti 4+ ion complex to obtain a precursor solution; adding a monomer compound and a crosslinking agent to the precursor solution and stirring; continuing to add an initiator to the precursor solution to initiate the polymerization reaction of the monomer compound and the crosslinking agent to obtain a blue gel; drying the blue gel to obtain a dry gel; putting the dry gel into a sintering furnace for roasting, and the sintering furnace is heated from room temperature to 650 °C to 850 °C and kept warm to obtain CaCu3Ti 4-x M x O 12 powder. This CaCu3Ti 4-x M x O 12 thermistor not only has a uniform chemical composition, a narrow grain size distribution of ceramic grains, but also is a compound with a single phase structure, and can well overcome the deficiency of the unsatisfactory product performance consistency caused by the non-uniform chemical composition and non-uniform microstructure of the mixture.
[0006] Patent CN116535203A discloses NTC thermistor ceramics, ceramic chips and preparation methods for rapid temperature measurement of electric water heaters. The invention is made of Co3O4, Mn3O4, NiO, Fe2O3, ZnO, MgO and rare earth element mineral salts. Due to the synergistic effect of MgO and rare earth element mineral salts, the NTC thermistor ceramics have high density, resistance to moisture and heat, and low aging rate.
[0007] Patent CN116813325A discloses a production process of thermosensitive ceramics. The invention allows the thermosensitive ceramic raw materials to stand still and be sealed to obtain the ingredients to be used; the ingredients to be used are weighed and mixed to obtain the mixture, the mixture is ball-milled with water, and dried to obtain the ball mill; the ball mill is sieved and pre-fired to obtain the pre-fired material; the mixture is mixed with water and ball-milled to obtain the second abrasive; the second abrasive is statically pressed and sintered to obtain the ceramic core ingot; the ceramic core ingot is cut into ceramic sheets, and then the silver paste is coated on the surface of the ceramic sheet, and the thermosensitive ceramic is obtained after curing and cutting. The raw materials of the thermosensitive ceramic are finer through two grindings, and the raw materials are fully mixed and evenly mixed, and the compatibility of the raw material system is further improved through preheating treatment, and the density of the obtained thermosensitive ceramic is improved, so that the thermosensitive ceramic obtains a better thermosensitive effect.
[0008] NTC ceramics are usually made from metal oxide powders through mixing, molding and sintering. In this process, the raw materials may contain moisture, volatiles or gases, which may form pores during the sintering process and affect the consistency of the ceramics. Therefore, it is of great significance to improve the consistency of thermistor technology. Summary of the invention
[0009] According to the shortcomings of the prior art, the present invention solves the problems existing in the negative temperature coefficient sintering process and reduces the overall porosity of the thermosensitive ceramic, thereby preparing aY2O3-bYCr with dense microstructure, stable electrical properties and good consistency. 0.5 Mn 0.5 O3 thermistor ceramics. Specifically, the technical solution of the present invention includes the following contents:
[0010] One of the purposes of the present invention is to provide a Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermal sensitive ceramic material, the Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic materials include the following raw materials:
[0011] Yttrium oxide, manganese tetraoxide, chromium oxide, and zirconium oxide;
[0012] The purity of the yttrium oxide, manganese tetraoxide, chromium oxide and zirconium oxide is ≥99%.
[0013] The second object of the present invention is to provide a Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 A method for preparing an O3 thermosensitive ceramic material, the method comprising the following steps:
[0014] Yttrium oxide, manganese tetraoxide and chromium oxide are placed in a ball mill as the first raw material, and the first slurry is obtained by ball milling with grinding balls for the first time. The first slurry is dried at 50°C to 120°C and then passed through a 100-mesh sieve to obtain a first mixed material. The first mixed material is calcined at a high temperature of 1000°C to 1300°C for 3h to 5h to obtain a conductive phase YCr 0.5 Mn 0.5 O3;
[0015] The conductive phase YCr 0.5 Mn 0.5 O3, yttrium oxide and zirconium oxide are used as the second raw materials and mixed by a second ball milling in a ball mill with grinding balls to obtain a second slurry, the second slurry is dried at 50° C. to 120° C. and then passed through a 100-mesh sieve to obtain a second mixed material, and the second mixed material is mixed with a binder to obtain a ceramic powder;
[0016] The ceramic powder is granulated and aged for 12 to 24 hours to obtain a pretreated ceramic powder, and the pretreated ceramic powder is dry cold isostatically pressed and dried to obtain a ceramic body; the ceramic body is sintered at a high temperature of 1550 to 1650 degrees Celsius for 3 to 5 hours to obtain the Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
[0017] Furthermore, the molar ratio of Y:Cr:Mn of yttrium oxide, trimanganese tetraoxide and chromium oxide in the first raw material is 2:1:1.
[0018] Furthermore, the conditions for the first ball milling mixing include that the ball milling medium is anhydrous ethanol, the mass ratio of the first raw material: the ball milling medium: the grinding ball is 1:1-4:0.8-2.5 and the ball milling time is 8h-36h.
[0019] Furthermore, the conductive phase YCr 0.5 Mn 0.5 The molar ratio of O3:yttria:zirconia is 0.4:0.6:0-0.15.
[0020] Preferably, the conductive phase YCr 0.5 Mn 0.5The molar ratio of O3:yttria:zirconia is 0.4:0.6:0.03-0.12.
[0021] Furthermore, the conditions for the second ball milling mixing include that the ball milling medium is anhydrous ethanol, the mass ratio of the second raw material: the ball milling medium: the grinding ball is 1:1-4:0.8-2.5 and the ball milling time is 8h-36h.
[0022] Furthermore, the binder is polyvinyl alcohol with a mass concentration of 5%.
[0023] Furthermore, the mass ratio of the second mixture to the binder is 1:0.05-0.15.
[0024] Furthermore, the conditions of the dry cold isostatic pressing include a molding pressure of 20 MPa to 30 MPa and a holding time of 30 s to 180 s.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The thermistor ceramics in the present invention are mainly composed of high resistance phase Y2O3 and conductive phase YCr 0.5 Mn 0.5 O3, while the doped ZrO2 is mainly located in the Y2O3 phase (Y 1-x Zr x )2O3 solid solution. The addition of ZrO2 reduces the melting point of the ZrO2-Y2O3 binary system and reduces the sintering temperature. 4+ Radius With Y 3+ Radius Similar, this ensures that Zr 4+ Replace Y 3+ The lattice distortion is small. In the final stage of sintering, a part of the grains with low surface energy tend to grow to a larger size at the consumption of the surrounding smaller grains, which is called discontinuous grain growth. In this process, due to the high mobility of the grain boundaries, the pores are easily enclosed in the grains, and the sintering is no longer densified. Since ZrO2 has a high melting point (2715℃), it is easy to form a solid solution at the grain boundary, and has a lower grain boundary migration speed than Y2O3, thereby hindering the migration of the grain boundary and the occurrence of secondary recrystallization, which is conducive to eliminating pores and uniform grain size, and improving the consistency of negative temperature coefficient thermistors.
[0027] (2) The raw materials used for the thermosensitive ceramic material in the present invention are all common oxides, and the preparation process is simple and the cost is low.
[0028] (3) Zr doping 4+ aY2O3-bYCr 0.5 Mn 0.5O3 thermistor ceramic material has high density, excellent electrical properties, and greatly improved consistency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The XRD patterns of the samples in Examples 1-6.
[0030] Figure 2 The SEM images of the samples in Examples 1-6 are shown in FIG. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0032] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0033] Yttrium oxide (Y2O3): purchased from Aladdin, purity ≥99.9%, CAS number 1314-36-9;
[0034] Chromium oxide (Cr2O3): purchased from Aladdin, purity ≥ 99.9%, CAS number 1333-82-0;
[0035] Manganese tetraoxide (Mn3O4): purchased from Aladdin, purity ≥ 99.9%, CAS number 1317-35-7;
[0036] Zirconium oxide (ZrO2): purchased from Aladdin, purity ≥ 99.9%, CAS number 1314-23-4.
[0037] Embodiment 1:
[0038] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O 33 The preparation of thermosensitive ceramic materials specifically includes the following processes:
[0039] First batching: Using an electronic analytical balance with an accuracy of 0.0001 g, Y2O3, Cr2O3 and Mn3O4 were weighed as the first raw material according to the pre-designed Y:Cr:Mn molar ratio of 2:1:1.
[0040] First mixing: The weighed first raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:1:0.8, the ball milling speed is 300r / min, and the ball milling time is controlled to be 8h. After the ball milling is completed, the obtained first slurry is placed in a drying oven and dried at 50°C for 12h. The dried powder is sieved through a 100-mesh sieve to obtain a uniform first mixed material.
[0041] Calcination: The first mixture was calcined at 1000°C for 3 hours to obtain the conductive phase YCr 0.5 Mn 0.5 O3.
[0042] Second batching: Use an electronic analytical balance with an accuracy of 0.0001g to measure the conductive phase YCr 0.5 Mn 0.5 O3:Y2O3 molar ratio 0.4:0.6 formula ratio molar weighing conductive phase YCr 0.5 Mn 0.5 O3 and Y2O3 are used as the second raw materials.
[0043] Second mixing: The weighed second raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:1:0.8, the ball milling speed is 300r / min, and the ball milling time is controlled to be 8h. After the ball milling is completed, the obtained second slurry is placed in a drying oven and dried at 50°C for 12h. The dried powder is sieved through a 100-mesh sieve to obtain the second mixed material.
[0044] Granulation and aging: Add 5% of the mass of the second mixed material to the screened second mixed material, and add a homemade 5% polyvinyl alcohol (PVA) solution as a binder, and fully mix in an agate mortar to obtain a ceramic powder. The mixed ceramic powder is placed on a tray for granulation, and aged for 12 hours after the granulation is completed to improve the molding performance of the ceramic powder, thereby obtaining a pretreated ceramic powder.
[0045] Molding and drying: Weigh a certain amount of pre-treated ceramic powder after aging, put it into a stainless steel mold, and use dry cold isostatic pressing to control the molding pressure to 20MPa and the holding time to 30ss. The ceramic body obtained after treatment is placed in a drying oven and dried at 100℃ for 24 hours until the body quality is stable.
[0046] Firing: The dried ceramic body was placed in a muffle furnace and sintered in an air atmosphere. The temperature was raised to 1200°C at a heating rate of 3°C / min, and then the heating rate was adjusted to 1°C / min to raise the temperature to 1550°C. The temperature was kept for 3 hours and cooled in the furnace to obtain Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
[0047] Embodiment 2:
[0048] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0049] First batching: Using an electronic analytical balance with an accuracy of 0.0001 g, Y2O3, Cr2O3 and Mn3O4 were weighed as the first raw material according to the pre-designed Y:Cr:Mn molar ratio of 2:1:1.
[0050] First mixing: The weighed first raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:1.5:1.5, the ball milling speed is 300r / min, and the ball milling time is controlled to be 12h. After the ball milling is completed, the obtained first slurry is placed in a drying oven and dried at 90°C for 12h. The dried powder is sieved through a 100-mesh sieve to obtain a uniform first mixed material.
[0051] Calcination: The first mixture was calcined at 1100°C for 4 h to obtain the conductive phase YCr 0.5 Mn 0.5 O3.
[0052] Second batching: Use an electronic analytical balance with an accuracy of 0.0001g to measure the conductive phase YCr 0.5 Mn 0.5 O3:Y2O3:ZrO2 molar ratio of 0.4:0.6:0.03 formula ratio molar weighing conductive phase YCr 0.5 Mn 0.5 O3, Y2O3 and ZrO2 are used as the second raw material.
[0053] Second mixing: The weighed second raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:1.5:1.5, the ball milling speed is 300r / min, and the ball milling time is controlled to be 12h. After the ball milling is completed, the obtained second slurry is placed in a drying oven and dried at 90°C for 12h. The dried powder is sieved through a 100-mesh sieve to obtain the second mixed material.
[0054] Granulation and aging: Add 10% of the mass of the second mixed material to the screened second mixed material, and add a homemade 5% polyvinyl alcohol (PVA) solution as a binder, and fully mix in an agate mortar to obtain a ceramic powder. The mixed ceramic powder is placed on a tray for granulation, and aged for 24 hours after granulation to improve the molding performance of the ceramic powder, thereby obtaining a pretreated ceramic powder.
[0055] Molding and drying: Weigh a certain amount of pre-treated ceramic powder that has been aged, put it into a stainless steel mold, and use dry cold isostatic pressing to control the molding pressure to 24MPa and the holding time to 60s. The ceramic body obtained after treatment is placed in a drying oven and dried at 100℃ for 24 hours until the body quality is stable.
[0056] Firing: The dried ceramic body was placed in a muffle furnace and sintered in an air atmosphere. The temperature was raised to 1200°C at a heating rate of 3°C / min, and then the heating rate was adjusted to 1°C / min to raise the temperature to 1600°C. The temperature was kept for 4 hours and cooled in the furnace to obtain Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
[0057] Embodiment 3:
[0058] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0059] First batching: Using an electronic analytical balance with an accuracy of 0.0001 g, Y2O3, Cr2O3 and Mn3O4 were weighed as the first raw material according to the pre-designed Y:Cr:Mn molar ratio of 2:1:1.
[0060] First mixing: The weighed first raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:2.5:2, the ball milling speed is 300r / min, and the ball milling time is controlled to be 24h. After the ball milling is completed, the obtained first slurry is placed in a drying oven and dried at 100℃ for 12h. The dried powder is sieved through a 100-mesh sieve to obtain a uniform first mixed material.
[0061] Calcination: The first mixture was calcined at 1200°C for 5 hours to obtain the conductive phase YCr 0.5 Mn 0.5 O3.
[0062] Second batching: Use an electronic analytical balance with an accuracy of 0.0001g to measure the conductive phase YCr 0.5 Mn 0.5 O3:Y2O3:ZrO2 molar ratio of 0.4:0.6:0.06 formula ratio molar weighing conductive phase YCr 0.5 Mn 0.5 O3, Y2O3 and ZrO2 are used as the second raw material.
[0063] Second mixing: The weighed second raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:2.5:2, the ball milling speed is 300r / min, and the ball milling time is controlled to be 24h. After the ball milling is completed, the obtained second slurry is placed in a drying oven and dried at 100℃ for 12h. The dried powder is sieved through a 100-mesh sieve to obtain the second mixed material.
[0064] Granulation and aging: Add 10% of the mass of the second mixed material to the screened second mixed material, and add a homemade 5% polyvinyl alcohol (PVA) solution as a binder, and fully mix in an agate mortar to obtain a ceramic powder. The mixed ceramic powder is placed on a tray for granulation, and aged for 24 hours after granulation to improve the molding performance of the ceramic powder, thereby obtaining a pretreated ceramic powder.
[0065] Molding and drying: Weigh a certain amount of pre-treated ceramic powder that has been aged, put it into a stainless steel mold, and use dry cold isostatic pressing to control the molding pressure to 28MPa and the holding time to 120s. The ceramic body obtained after treatment is placed in a drying oven and dried at 100℃ for 24 hours until the body quality is stable.
[0066] Firing: The dried ceramic body was placed in a muffle furnace and sintered in an air atmosphere. The temperature was raised to 1200°C at a heating rate of 3°C / min, and then the heating rate was adjusted to 1°C / min to raise the temperature to 1600°C. The temperature was kept for 5 hours and cooled in the furnace to obtain Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
[0067] Embodiment 4:
[0068] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0069] First batching: Using an electronic analytical balance with an accuracy of 0.0001 g, Y2O3, Cr2O3 and Mn3O4 were weighed as the first raw material according to the pre-designed Y:Cr:Mn molar ratio of 2:1:1.
[0070] First mixing: The weighed first raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:4:2.5, the ball milling speed is 300r / min, and the ball milling time is controlled to be 36h. After the ball milling is completed, the obtained first slurry is placed in a drying oven and dried at 120℃ for 12h. The dried powder is sieved through a 100-mesh sieve to obtain a uniform first mixed material.
[0071] Calcination: The first mixture was calcined at 1300°C for 5 hours to obtain the conductive phase YCr 0.5 Mn 0.5 O3.
[0072] Second batching: Use an electronic analytical balance with an accuracy of 0.0001g to measure the conductive phase YCr 0.5 Mn 0.5 O3:Y2O3:ZrO2 molar ratio of 0.4:0.6:0.09 formula ratio molar weighing conductive phase YCr 0.5 Mn 0.5 O3, Y2O3 and ZrO2 are used as the second raw material.
[0073] Second mixing: The weighed second raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:4:2.5, the ball milling speed is 300r / min, and the ball milling time is controlled to be 36h. After the ball milling is completed, the obtained second slurry is placed in a drying oven and dried at 120℃ for 12h. The dried powder is sieved through a 100-mesh sieve to obtain the second mixed material.
[0074] Granulation and aging: 15% of the mass of the second mixed material is added to the screened second mixed material, and a homemade 5% polyvinyl alcohol (PVA) solution is added as a binder, and the mixture is fully mixed in an agate mortar to obtain a ceramic powder. The mixed ceramic powder is placed on a tray for granulation, and aged for 24 hours after the granulation is completed to improve the molding performance of the ceramic powder, thereby obtaining a pretreated ceramic powder.
[0075] Molding and drying: Weigh a certain amount of pre-treated ceramic powder that has been aged, put it into a stainless steel mold, and use dry cold isostatic pressing to control the molding pressure to 30MPa and the holding time to 180s. The ceramic body obtained after treatment is placed in a drying oven and dried at 100℃ for 24 hours until the body quality is stable.
[0076] Firing: The dried ceramic body was placed in a muffle furnace and sintered in an air atmosphere. The temperature was raised to 1200°C at a heating rate of 3°C / min, and then the heating rate was adjusted to 1°C / min to raise the temperature to 1650°C. The temperature was kept for 5 hours and cooled in the furnace to obtain Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
[0077] Embodiment 5:
[0078] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0079] First batching: Using an electronic analytical balance with an accuracy of 0.0001 g, Y2O3, Cr2O3 and Mn3O4 were weighed as the first raw material according to the pre-designed Y:Cr:Mn molar ratio of 2:1:1.
[0080] First mixing: The weighed first raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:4:2.5, the ball milling speed is 300r / min, and the ball milling time is controlled to be 36h. After the ball milling is completed, the obtained first slurry is placed in a drying oven and dried at 120℃ for 12h. The dried powder is sieved through a 100-mesh sieve to obtain a uniform first mixed material.
[0081] Calcination: The first mixture was calcined at 1300°C for 5 hours to obtain the conductive phase YCr 0.5 Mn 0.5 O3.
[0082] Second batching: Use an electronic analytical balance with an accuracy of 0.0001g to measure the conductive phase YCr 0.5 Mn 0.5 O3:Y2O3:ZrO2 molar ratio of 0.4:0.6:0.12 formula ratio molar weighing conductive phase YCr 0.5 Mn 0.5 O3, Y2O3 and ZrO2 are used as the second raw material.
[0083] Second mixing: The weighed second raw material is placed in an XGB2 planetary ball mill, and anhydrous ethanol is used as the ball milling medium for ball milling and mixing. The mass ratio of the first raw material, the ball milling medium and the grinding ball is controlled to be 1:4:2.5, the ball milling speed is 300r / min, and the ball milling time is controlled to be 36h. After the ball milling is completed, the obtained second slurry is placed in a drying oven and dried at 120℃ for 12h. The dried powder is sieved through a 100-mesh sieve to obtain the second mixed material.
[0084] Granulation and aging: 15% of the mass of the second mixed material is added to the screened second mixed material, and a homemade 5% polyvinyl alcohol (PVA) solution is added as a binder, and the mixture is fully mixed in an agate mortar to obtain a ceramic powder. The mixed ceramic powder is placed on a tray for granulation, and aged for 24 hours after the granulation is completed to improve the molding performance of the ceramic powder, thereby obtaining a pretreated ceramic powder.
[0085] Molding and drying: Weigh a certain amount of pre-treated ceramic powder that has been aged, put it into a stainless steel mold, and use dry cold isostatic pressing to control the molding pressure to 30MPa and the holding time to 180s. The ceramic body obtained after treatment is placed in a drying oven and dried at 100℃ for 24 hours until the body quality is stable.
[0086] Firing: The dried ceramic body was placed in a muffle furnace and sintered in an air atmosphere. The temperature was raised to 1200°C at a heating rate of 3°C / min, and then the heating rate was adjusted to 1°C / min to raise the temperature to 1650°C. The temperature was kept for 5 hours and cooled in the furnace to obtain Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
[0087] Embodiment 6:
[0088] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0089] The amount of zirconium oxide in Example 4 was increased from 0.09 mol to 0.15 mol, and the other conditions remained the same as in Example 4.
[0090] Comparative Example 1:
[0091] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0092] The conductive phase YCr in Example 1 0.5 Mn 0.5 The molar ratio of O3:Y2O3 was adjusted from 0.4:0.6 to 0.3:0.7, and the other conditions remained the same as in Example 1.
[0093] Comparative Example 2:
[0094] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0095] The conductive phase YCr in Example 2 0.5 Mn 0.5 The molar ratio of O3:Y2O3 was adjusted from 0.4:0.6 to 0.3:0.7, and the other conditions remained the same as in Example 2.
[0096] Comparative Example 3:
[0097] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0098] The conductive phase YCr in Example 3 0.5 Mn 0.5 The molar ratio of O3:Y2O3 was adjusted from 0.4:0.6 to 0.3:0.7, and the other conditions remained the same as in Example 3.
[0099] Comparative Example 4:
[0100] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0101] The conductive phase YCr in Example 4 0.5 Mn 0.5 The molar ratio of O3:Y2O3 was adjusted from 0.4:0.6 to 0.3:0.7, and the other conditions remained the same as in Example 4.
[0102] Comparative Example 5:
[0103] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0104] The conductive phase YCr in Example 5 0.5 Mn 0.5 The molar ratio of O3:Y2O3 was adjusted from 0.4:0.6 to 0.3:0.7, and the other conditions remained the same as in Example 5.
[0105] Comparative Example 6:
[0106] A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0107] The conductive phase YCr in Example 6 0.5 Mn 0.5 The molar ratio of O3:Y2O3 was adjusted from 0.4:0.6 to 0.3:0.7, and the other conditions remained the same as in Example 6.
[0108] Comparative Example 7:
[0109] A Ca 2+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0110] The zirconium oxide in Example 3 was replaced by calcium oxide, and the other conditions remained the same as in Example 3.
[0111] Comparative Example 8:
[0112] A Sr 2+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation of O3 thermistor ceramic materials specifically includes the following processes:
[0113] The zirconium oxide in Example 3 was replaced by strontium oxide, and the other conditions remained the same as those in Example 3.
[0114] Detection of Zr obtained in Examples 1 to 6 and Comparative Examples 1 to 6 4+ Doped Y2O3-YCr 0.5 Mn 0.5 O3 thermal-sensitive ceramic material, Ca obtained in Comparative Example 7 2+ Doped Y2O3-YCr 0.5 Mn 0.5 O3 thermosensitive ceramic material and Sr obtained in Comparative Example 8 2+ Doped aY2O3-bYCr 0.5 Mn 0.5 The resistivity, B25 / 50 value, density and consistency of O3 thermistor ceramic materials are shown in Table 1 below.
[0115] Table 1
[0116]
[0117] From the test data in Table 1, we can find that:
[0118] (1) Within the formulation range designed by the present invention, the Zr obtained in Examples 1 to 5 4+ Doped Y2O3-YCr 0.5 Mn 0.5 O3 thermistor ceramic material has lower resistivity and good consistency improvement.
[0119] (2) It can be seen from Example 6 that when the amount of zirconium oxide is further increased, the resistivity is greatly improved, and the consistency is significantly reduced, which is not conducive to Y2O3-YCr 0.5 Mn 0.5 The consistency of O3 thermistor ceramic materials is improved.
[0120] (3) It can be seen from comparative examples 1 to 6 that when the conductive phase YCr is reduced 0.5 Mn 0.5When the usage of ZrO3 is increased and the usage of Y2O3 is increased, zirconium doping can still improve the consistency of the thermistor ceramics, but the resistivity of the thermistor ceramics is relatively high. Similarly, when the usage of zirconium oxide is further increased (Comparative Example 6), the consistency of the thermistor ceramics is reduced, which is not conducive to improving the consistency of the thermistor ceramics.
[0121] (4) From Comparative Example 7, it can be seen that the small atom Ca 2+ The doping effect of Zr in the formulation process system of the present invention is much lower than that of Zr with the same size. 4+ The doping effect.
[0122] (5) Comparative Example 8 shows that due to the high grain boundary migration rate of strontium oxide, it is easy to produce closed pores at the grain boundaries after doping, which has adverse effects on the performance of the thermistor ceramics, resulting in poor consistency of the thermistor ceramics finally prepared.
[0123] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
Claims
1. A Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material, characterized in that: The Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic materials include the following raw materials: Yttrium oxide, manganese tetraoxide, chromium oxide, and zirconium oxide; The purity of the yttrium oxide, manganese tetraoxide, chromium oxide and zirconium oxide is ≥99%.
2. A Zr as claimed in claim 1 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 The preparation method of O3 thermistor ceramic material is characterized in that: The preparation method comprises the following steps: Yttrium oxide, manganese tetraoxide and chromium oxide are placed in a ball mill as the first raw material, and the first slurry is obtained by ball milling with grinding balls for the first time. The first slurry is dried at 50°C to 120°C and then passed through a 100-mesh sieve to obtain a first mixed material. The first mixed material is calcined at a high temperature of 1000°C to 1300°C for 3h to 5h to obtain a conductive phase YCr 0.5 Mn 0.5 O3; The conductive phase YCr 0.5 Mn 0.5 O3, yttrium oxide and zirconium oxide are used as the second raw materials and mixed by a second ball milling in a ball mill with grinding balls to obtain a second slurry, the second slurry is dried at 50° C. to 120° C. and then passed through a 100-mesh sieve to obtain a second mixed material, and the second mixed material is mixed with a binder to obtain a ceramic powder; The ceramic powder is granulated and aged for 12h to 24h to obtain a pretreated ceramic powder, and the pretreated ceramic powder is dry cold isostatically pressed and dried to obtain a ceramic body; the ceramic body is sintered at a high temperature of 1550° C. to 1650° C. for 3h to 5h to obtain the Zr 4+ Doped aY2O3-bYCr 0.5 Mn 0.5 O3 thermistor ceramic material.
3. The preparation method according to claim 2, characterized in that: The molar ratio of Y:Cr:Mn among yttrium oxide, trimanganese tetraoxide and chromium oxide in the first raw material is 2:1:
1.
4. The preparation method according to claim 2, characterized in that: The conditions for the first ball milling mixing include that the ball milling medium is anhydrous ethanol, the mass ratio of the first raw material: the ball milling medium: the grinding ball is 1:1-4:0.8-2.5 and the ball milling time is 8h-36h.
5. The preparation method according to claim 2, characterized in that: The conductive phase YCr 0.5 Mn 0.5 The molar ratio of O3: yttria: zirconium oxide is 0.4:0.6:0~0.
15.
6. The preparation method according to claim 2, characterized in that: The conditions for the second ball milling mixing include that the ball milling medium is anhydrous ethanol, the mass ratio of the second raw material: the ball milling medium: the grinding ball is 1:1~4:0.8~2.5 and the ball milling time is 8h~36h.
7. The preparation method according to claim 2, characterized in that: The binder is polyvinyl alcohol with a mass concentration of 5%.
8. The preparation method according to claim 2, characterized in that: The mass ratio of the second mixture to the binder is 1:0.05-0.
15.
9. The preparation method according to claim 2, characterized in that: The conditions of the dry cold isostatic pressing include a molding pressure of 20 MPa to 30 MPa and a holding time of 30 s to 180 s.
Citation Information
Patent Citations
Wide-warm-area negative temperature coefficient thermistor material
CN102627458A
High-temperature thermistor material and preparation method thereof
CN104557040A
Reduction resistant thermistor, method of production thereof, and temperature sensor
US20020036563A1